2010
DOI: 10.1111/j.1439-0531.2010.01710.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ovine Granulocyte‐Macrophage Colony‐stimulating Factor on Bovine In Vitro Embryo Development and Blastocyst Interferon‐τ Secretion

Abstract: This experiment examined the effects of including recombinant ovine granulocyte-macrophage colony-stimulating factor (GMCSF) in in vitro culture on secretion of interferon-τ (IFNT) by bovine blastocysts. At 32 h post-insemination (p.i.), cleaved bovine zygotes were selected and incubated with or without GMCSF for either 48 h only (between 32 and 80 h p.i., Early) or until day 9 p.i. (Throughout). Concentrations of GMCSF (ng/ml) examined were as follows: Experiment 1: 2, 5, 10 and 50 (Early only); Experiment 2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
(156 reference statements)
0
6
0
Order By: Relevance
“…Nine batches of ovaries (total of 546 ovaries) were collected at a local abattoir from Bos taurus cows (mixed breeds). Details of oocyte recovery and subsequent in vitro maturation, fertilization, and culture procedures have been described . At 48 hr post‐insemination (p.i.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine batches of ovaries (total of 546 ovaries) were collected at a local abattoir from Bos taurus cows (mixed breeds). Details of oocyte recovery and subsequent in vitro maturation, fertilization, and culture procedures have been described . At 48 hr post‐insemination (p.i.…”
Section: Methodsmentioning
confidence: 99%
“…At 186 ( n = 57) and 210 ( n = 53) hr p.i., blastocysts were evaluated in terms of their stage of development, zona‐inclusive diameter and quality score . Blastocysts were allocated (average of 12 derived from each batch of ovaries) to either a control (38.5°C for 24 hr) or heat‐shock treatment (42°C for 4 hr followed by 38.5°C for 20 hr), ensuring treatments were balanced in terms of overall blastocyst quality.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that CSF2 supplementation will improve IVP blastocyst development in the mouse [ 22 ], pig [ 23 , 24 ], and human [ 25 ], but it is less clear whether CSF2 contains this activity in bovine embryos. Some of the initial work on CSF2 supplementation found that IVP bovine blastocyst formation could be improved with CSF treatment [ 26 , 27 , 28 ], but more recent work failed to consistently detect these effects [ 29 , 30 , 31 , 32 ]. One general observation is that CSF2 is more likely to improve blastocyst formation when development rates are low, suggesting that CSF2 may only function when embryos are under some type of developmental or environmental stress that limits developmental potential.…”
Section: Colony Stimulating Factormentioning
confidence: 99%
“…GM‐CSF and GM‐CSF receptor α (GM‐CSFRα) have been shown to be expressed in human and murine placenta, including embryonic trophoblast cells, throughout gestation (for review, Robertson 2007), and to play pivotal roles in the regulation of the uterine leukocyte population, pre‐implantation embryo development, and placental morphogenesis and function (Robertson 2007; Neira et al . 2010; Hickman et al . 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a hematopoietic cytokine that was originally defined by induction from bone marrow precursor cells to granulocyte and macrophage colonies, and GM-CSF is now known as a multifunctional cytokine that regulates survival, proliferation, differentiation, and the effector functions of neutrophils, macrophages, eosinophils, and dendritic cells (Metcalf 1989;Gasson 1991). GM-CSF and GM-CSF receptor a (GM-CSFRa) have been shown to be expressed in human and murine placenta, including embryonic trophoblast cells, throughout gestation (for review, Robertson 2007), and to play pivotal roles in the regulation of the uterine leukocyte population, pre-implantation embryo development, and placental morphogenesis and function (Robertson 2007;Neira et al 2010;Hickman et al 2011). GM-CSF treatment reduces early embryo malformation and spontaneous embryo loss in the CBA/J ¥ DBA/2 mating combination (Tartakovsky and Ben-Yair 1991), and protects mice from teratogen-induced embryo malformation (Savion et al 2003).…”
Section: Introductionmentioning
confidence: 99%